2005
DOI: 10.1017/s1049023x00002818
|View full text |Cite
|
Sign up to set email alerts
|

Blackout 2003: Preparedness and Lessons Learned from the Perspectives of Four Hospitals

Abstract: Introduction:The blackout in North America of August 2003 was one of the worst on record. It affected eight United States states and parts of Canada for >24 hours. Additionally, two large United States cities, Detroit, Michigan and Cleveland, Ohio, suffered from a loss of water pressure and a subsequent ban on the use of public supplies of potable water that lasted four days. A literature review revealed a paucity of literature that describes blackouts and how they may affect the medical community.Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 1 publication
2
43
0
Order By: Relevance
“…With limited outside sources of prepared food coupled with long work hours, facilities should expect to feed staff 24 hours a day. 37 The most important principle is to make safety the first consideration-in all situations. A necessary part of the overall security system is to supply some type of identificationpreferably in a format that cannot be easily copied-to those volunteers who have authorization to enter the healthcare facility.…”
Section: Supporting the Augmenteesmentioning
confidence: 99%
“…With limited outside sources of prepared food coupled with long work hours, facilities should expect to feed staff 24 hours a day. 37 The most important principle is to make safety the first consideration-in all situations. A necessary part of the overall security system is to supply some type of identificationpreferably in a format that cannot be easily copied-to those volunteers who have authorization to enter the healthcare facility.…”
Section: Supporting the Augmenteesmentioning
confidence: 99%
“…6 Klein et al documented that while the power outage increased the utilization of hospitals' emergency services, the effective operation of hospitals was compromised by the loss of power. 7 Beatty and colleagues described the public health responses in NYC to risks posed by the power outage, such as spoilage of food and contamination and/or lack of water. 8 The increases in health service provider activity reported by these studies suggest an increase in health problems associated with the blackout, but only one study reported actual cases of illness.…”
mentioning
confidence: 99%
“…Other reviews of adverse effects on hospital operations during natural disasters have included discussions of the consequences stemming from loss of water. Researchers detailed the effect of the 2003 blackout in the northeastern United States on four inner‐city hospitals (Klein et al, 2005). They reported on hospital equipment and operations that could not function because of lack of water.…”
Section: Water Supply Interruption May Severely Compromise the Operatmentioning
confidence: 99%